The Effect of Self-Efficacy on Engine Cadets’ Language Anxiety and Speaking Accuracy in Maritime Radio Communication - Mutmainnah Hasyari; Edi Wahyono (Indonesian Journal of Learning Studies, 2026)
Abstract Radio communication plays a vital role in engine room operations, where accurate delivery of technical information is essential for ship safety and efficiency. However, engine cadets often experience communication anxiety when reporting machinery conditions through radio systems, particularly under operational pressure. This study aims to examine the effect of communication anxiety on radio communication accuracy among engine cadets, with self-efficacy serving as a mediating variable. This study employed a quantitative explanatory research design involving approximately 100 engine cadets. Data were collected using structured questionnaires to measure communication anxiety and self-efficacy, as well as performance-based assessments of radio communication accuracy conducted through simulated normal and emergency engine room scenarios. The data were analyzed using mediation analysis through regression procedures. The findings reveal that communication anxiety has a significant negative effect on self-efficacy and radio communication accuracy. Self-efficacy demonstrates a significant positive influence on communication accuracy and partially mediates the relationship between communication anxiety and communication accuracy. These results indicate that psychological readiness plays a crucial role in technical radio communication performance among engine cadets. This study contributes to maritime education by emphasizing the importance of integrating psychological factors, particularly self-efficacy development, into engine cadets’ radio communication training to enhance accuracy and operational safety. Keywords: Communication language anxiety, Self-efficacy, Engine cadets, Radio communication